Improvement of short-term memory performance in aged beagles by a nutraceutical supplement containing phosphatidylserine, Ginkgo biloba, vitamin E, and pyridoxine - Araujo, Joseph A. (Canadian Veterinary Medical Association, 2008)
Aged dogs demonstrate cognitive decline that is linked to brain aging. The purpose of the present study was to examine if a commercially available nutraceutical supplement that may be neuroprotective and contains phosphatidylserine, Ginkgo biloba, vitamin E, and pyridoxine could improve cognitive function in aged beagles. Nine aged beagles were tested on performance on a delayed-non-matching-to-position task, which is a neuropsychological test of short-term visuospatial memory. All subjects were tested on 5 baseline sessions; then, to assess the supplement, a crossover design was used in which 1 group received the supplement and the other a control substance in the 1st phase, with treatment conditions being reversed in the 2nd phase. Performance accuracy was significantly improved in supplemented dogs compared with control dogs and the effect was long lasting. These findings suggest that the nutraceutical supplement can improve memory in aged dogs.